2006
DOI: 10.1002/pts.735
|View full text |Cite
|
Sign up to set email alerts
|

Effect of modified atmosphere packaging and superchilled storage on the shelf-life of farmed ready-to-cook spotted wolf-fish (Anarhichas minor)

Abstract: Modified atmosphere packaging (MAP) combined with superchilling (−1°C) was evaluated as a mild preservation method for farmed spotted wolf-fish (Anarhichas minor). Portions were packaged in air and in CO 2 : N 2 (60% : 40%) atmosphere with a gas : product ratio of approximately 1, at superchilled (−1.0°C ± 0.2°C) or chilled (+4.0°C ± 0.2°C) temperatures. A reduced bacterial growth (p < 0.001), measured as aerobic plate counts (APC) and psychrotrophic bacteria, was observed in modified atmosphere (MA) packaged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 26 publications
(28 reference statements)
1
18
0
Order By: Relevance
“…This might be because of vacuum effect, as a result of CO 2 absorption into the product. Such vacuum effect is also reported for MAP chicken, and increased liquid loss is also reported for wolf‐fish packaged in modified atmosphere compared to storage in air . Some of the liquid loss might also have taken place during the transport and temporary storage prior repackaging into MAP.…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…This might be because of vacuum effect, as a result of CO 2 absorption into the product. Such vacuum effect is also reported for MAP chicken, and increased liquid loss is also reported for wolf‐fish packaged in modified atmosphere compared to storage in air . Some of the liquid loss might also have taken place during the transport and temporary storage prior repackaging into MAP.…”
Section: Resultsmentioning
confidence: 63%
“…Furthermore, it is a pronounced interest in selling the fish pre‐packaged into consumer sized packages, either by use of air inside the package, vacuum packaging, skin pack or modified atmosphere packaging (MAP). The MAP method by its content of carbon dioxide (CO 2 ) inhibits bacterial growth and thus facilitates prolonged shelf life . MAP of farmed Atlantic cod has also shown that high levels of oxygen (O 2 ) together with CO 2 , give optimal quality preservation, which can also be applied to wild caught cod.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly to our results the super chilled storage at -2.2°C of fillet portions of farmed Atlantic cod (Gadus morhua) showed increased shelf life with respect to reduced growth of sulphide producing bacteria compared to ice chilled [36]; super chilled (-1.5°C) storage of aerobically packed cod (Gadus morhua) fillets was characterized by the growth of specific spoilage organisms and the production of microbial metabolites measured by an electronic nose [49]. When supper chilling combines with natural additives, and modified atmosphere packaging (MAP) the shelf-life prolongs to 22 days of Fernández [50] to 24 days to Sivertsvik [51] for Atlantic salmon (Salmo salar) fillets, and to 13 days only for farmed spotted wolf-fish (Anarhichas minor) [52] (Table 3).…”
Section: Total Plate Count Of Facultative Anaerobic and Psychrotrophimentioning
confidence: 99%
“…To extend the shelf life, vacuum packaging (VP) and packaging under modified atmospheres have been investigated. Modified atmosphere packaging (MAP) with carbon dioxide as an active gas component has been widely reported to inhibit microbial growth on fish, especially against Gram-negative spoilage bacteria (Goulas & Kontominas, 2007;Hovda, Sivertsvik, Lunestad, Lorentzen, & Rosens, 2007;Rosnes, Kleiberg, Sivertsvik, Lunestad, & Lorentzen, 2006;Sivertsvik, 2007;Stamatis & Arkoudelos, 2007;Stammen et al, 1990). Inhibition of the microbial population by CO 2 MAP resulted in significant improvements of sensory attributes of fish fillets due to the reduction of off-flavor compound formation when compared with air packaging (Goula & Kontominas, 2007).…”
Section: Introductionmentioning
confidence: 97%